The C-Terminus of Panusin, a Lobster β-Defensin, Is Crucial for Optimal Antimicrobial Activity and Serum Stability - Roberto Bello-Madruga; Javier Valle; M. Ángeles Jiménez; Marc Torrent; Vivian Montero-Alejo; David Andreu (MDPI AG, 2023)
β-defensins are one of the most abundant and studied families of antimicrobial peptides (AMPs). Because of their selective toxicity to bacterial membranes and a broad spectrum of microbicidal action, β-defensins are regarded as potential therapeutic agents. This work focuses on a β-defensin-like AMP from the spiny lobster Panulirus argus (hereafter referred to as panusin or PaD). This AMP is structurally related to mammalian defensins via the presence of an αβ domain stabilized by disulfide bonds. Previous studies of PaD suggest that its C-terminus (Ct_PaD) contains the main structural determinants of antibacterial activity. To confirm this hypothesis, we made synthetic versions of PaD and Ct_PaD to determine the influence of the C-terminus on antimicrobial activity, cytotoxicity, proteolytic stability, and 3D structure. After successful solid-phase synthesis and folding, antibacterial assays of both peptides showed truncated Ct_PaD to be more active than native PaD, confirming the role of the C-terminus in activity and suggesting that cationic residues in that region enhance binding to negatively charged membranes. On the other hand, neither PaD nor Ct_PaD were hemolytic or cytotoxic in human cells. Proteolysis in human serum was also studied, showing high (>24 h) t1/2 values for PaD and lower but still considerable for Ct_PaD, indicating that the missing native disulfide bond in Ct_PaD alters protease resistance, albeit not decisively. NMR-2D experiments in water agree with the results obtained by circular dichroism (CD), where in SDS micelles, CD showed both peptides adopting an increasingly ordered structure in a hydrophobic environment, in tune with their ability to perturb bacterial membrane systems. In conclusion, while the β-defensin features of PaD are confirmed as advantageous in terms of antimicrobial activity, toxicity, and protease stability, the results of the present work suggest that these same features are preserved, even enhanced, in the structurally simpler Ct_PaD, which must therefore be viewed as a valuable lead for the development of novel anti-infectives.